(untitled) (International Journal of Engineering and Computer Science, 2025)
The article examines the role of testing in ensuring software security, a topic of growing relevance due to the increasing complexity of IT systems and the rise in cyber threats. Software has become a critical component of enterprise infrastructure, government institutions, and everyday human life. Therefore, ensuring software security through effective testing has become one of the key priorities in the modern IT industry. This study explores contemporary security testing methods, encompassing both traditional approaches such as functional testing, penetration testing, static and dynamic code analysis, as well as modern automation techniques leveraging machine learning algorithms. A comprehensive analysis of publicly available scientific publications was conducted, focusing on the integration of security testing into the software development lifecycle (SDLC), with an emphasis on CI/CD practices, distributed testing, and continuous monitoring. The practical significance of this research lies in the applicability of the examined approaches to enhancing the security of information systems in a rapidly evolving IT landscape. The article will be of interest to cybersecurity specialists, lead developers, testing methodology researchers, and academics seeking to integrate advanced testing approaches into strategic cybersecurity measures for software systems.